Stufentherapie der COPD - Watz, Henrik; Kirsten, Anne; Greulich, Timm (DMW - Deutsche Medizinische Wochenschrift, 2019)
The goal of pharmacologic therapy of stable chronic obstructive pulmonary disease (COPD) is to reduce symptoms, improve exercise intolerance and health-related quality of life, and to reduce exacerbations. Inhaled long-acting β2-agonists (LABAs) and long-acting muscarinic antagonists (LAMAs) are equally effective for the symptomatic management of COPD. However, LAMAs are more effective than LABAs in the reduction of exacerbations. In patients with symptomatic COPD pharmacologic therapy is usually escalated using the fixed combination of LAMAs and LABAs (dual bronchodilation), which is also superior to LAMA monotherapy in the prevention of exacerbations. Adding inhaled corticosteroids (ICS) to LABA and LAMA (triple therapy) for a prevention of exacerbations results in a further reduction of exacerbations, especially in those patients with higher blood eosinophil counts. Non-pharmacologic management of COPD patients includes smoking cessation programs, vaccination, pulmonary rehabilitation, and strategies to improve or maintain their physical activity.
Keywords: chronisch obstruktive Bronchitis; Lungenemphysem; medikamentöse Behandlung; nicht medikamentöse Behandlung